Proceedings of the 4th International Conference on Mobile and Ubiquitous Multimedia - MUM '05 2005
DOI: 10.1145/1149488.1149503
|View full text |Cite
|
Sign up to set email alerts
|

User experiences with mobile phone camera game interfaces

Abstract: This paper presents the findings of a comparative study investigating different input interfaces for a mobile phone games application. A standard mobile phone joystick interface is compared with a phone camera interface to detect the phone translation and tilt to control a ball's movement within various levels of difficulty of a virtual maze game. Game completion times together with the resultant user experience for each of the games was collected during the studies. Results indicate that the joystick control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Their research showed that mobile devices are easy to manoeuvre and this translates into using tilt-input for a variety of interactions, including panning [3]. Panning is the use of a device's camera or position sensor to track a user's movements and convert them to the movements of a controlled view in the game.…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Their research showed that mobile devices are easy to manoeuvre and this translates into using tilt-input for a variety of interactions, including panning [3]. Panning is the use of a device's camera or position sensor to track a user's movements and convert them to the movements of a controlled view in the game.…”
Section: A Related Workmentioning
confidence: 99%
“…It is worth mentioning as well that while most research using device tilt as an input control uses data from a built-in sensor -typically an accelerometer -some research on tilt input uses the device's camera combined with image processing to compute the device's position and movement [e.g., 3,7,12,14,18]. The main disadvantage in using camera data is the substantial processing required in converting camera images to device movement.…”
Section: A Related Workmentioning
confidence: 99%
“…Reference [21] presents a gestural interface for a mobile phone games application, or specifically a maze game at which the user controls the movement of a ball through a maze. A camera on the phone which is looking at a visual code marker is used to detect tilt and translation of the phone, resulting in the ball movement.…”
Section: Related Workmentioning
confidence: 99%
“…The player moves around this mixed-reality space by moving his phone and firing using the centre key of the joy pad. Other games have evolved to use visual codes to either detect movement [9], to imply, locate, or interact with objects such as ConQwest by Area Code [3].…”
Section: Other Phone Camera Gamesmentioning
confidence: 99%